Evaluation of 10 years of parainfluenza virus, human metapneumovirus, and respiratory syncytial virus infections in lung transplant recipients - de Zwart, Auke E. S. (Am J Transplant, 2020)
Respiratory tract infection with pneumoviruses (PVs) and paramyxoviruses (PMVs) are increasingly associated with chronic lung allograft dysfunction (CLAD) in lung transplant recipients (LTRs). Ribavirin may be a treatment option but its effectiveness is unclear, especially with respect to infection severity. We retrospectively analyzed 10 years of PV/PMV infections in LTRs. The main end points were forced expiratory volume in 1 second (FEV(1)) at 3 and 6 months postinfection, expressed as a percentage of pre‐infection FEV(1) and incidence of new or progressed CLAD 6 months postinfection. A total of 139 infections were included: 88 severe infections (63%) (defined as >10% FEV(1) loss at infection) and 51 mild infections (37%) (≤10% FEV(1) loss). Overall postinfection CLAD incidence was 20%. Associations were estimated on postinfection FEV(1) for ribavirin vs no ribavirin (+13.2% [95% CI: 7.79; 18.67]) and severe vs mild infection (−11.1% [95% CI: −14.76; −7.37]). Factors associated with CLAD incidence at 6 months were ribavirin treatment (odds ratio (OR [95% CI]) 0.24 [0.10; 0.59]), severe infection (OR [95% CI] 4.63 [1.66; 12.88]), and mycophenolate mofetil use (OR [95% CI] 0.38 [0.14; 0.97]). These data provide valuable information about the outcomes of lung transplant recipients with these infections and suggests possible associations of ribavirin use and infection severity with long‐term outcomes. Well‐designed prospective trials are needed to confirm these findings.